Cardiac ageing: from hallmarks to therapeutic opportunities - Hastings, Margaret H.; Zhou, Qiulian; Wu, Chao; Shabani, Parisa; Huang, Shengyuan; Yu, Xuejing; Singh, Anand P; Guseh, J Sawalla; Li, Haobo; Lerchenmüller, Carolin; Rosenzweig, Anthony (Cardiovascular research, 2024)
Cardiac ageing is an intricate and multifaceted process with considerable impact on public health, especially given the global demographic shift towards aged populations. This review discusses structural, cellular, and functional changes associated with cardiac ageing and heart failure with preserved ejection fraction (HFpEF). Key molecular mediators are considered within the framework of the established hallmarks of ageing, with particular attention to promising therapeutic candidates. We further delineate the differential impacts of ageing on cardiac structure and function in men and women, addressing hormonal and chromosomal influences. The protective and mitigating effects of exercise in cardiac ageing and HFpEF in particular are discussed, as an inspiration for the identification of pathways that mitigate biological ageing. We also emphasize how much remains to be learned and the importance of these efforts in enhancing the cardiac health of ageing populations worldwide.
Gesehen am 04.11.2024